Pengembangan Kompetensi Professionalisme Guru Madrasah Melalui Pelatihan Penelitian Tindakan Kelas (PTK) - Habib Husnial Pardi (Prodi Tadris Matematika-UIN Mataram, 2021)
Madrasah Aliyah Bayyinul Ulum Santong has quite a number of certified teachers as capital in developing madrasas to become excellent madrasas. Human resources: teachers as a strategic component in supporting the quality of learning need to be improved on an ongoing basis, one of which is training or Classroom Action Research (CAR) workshops. This activity aims to improve the quality of learning in the classroom. The participants in this activity were all 14 subject certification teachers in the Madrasah Aliyah Bayyinul Ulum environment. The method of activities used is workshops and training with 3 main activities, namely deepening the material and compiling the PTK proposal through workshops, planning PTK through group discussion activities (Focus Group discussions), and implementing PTK through guidance on the implementation of PTK. The result is that the teachers understand better CAR, and realize the urgency of CAR in improving the quality of learning in the classroom. With the practical ability to compile proposals and to be followed up by research activities, a research culture will be built among teachers as a solution in solving various learning problems which in turn will increase the competence of teacher professionalism itself